UI/UX IMPLEMENTASI METODE HALAQAH PADA APLIKASI QURAN TAHFIDZ - Fajarini, Dianingtyas; Haryono, Kholid (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The activity of memorizing the Al-Qur’an is now increasing in popularity among society. There are various methods used in the process of memorizing the Al-Qur'an, one of which is the halaqah method. This method facilitates interaction between teachers and students, making it very suitable for application in educational institutions or communities such as Islamic boarding schools, tahfidz schools, community tahfidz groups in mosques. However, challenges arise when a teacher has to manage many students in one halaqah, making this method less efficient for large groups. This problem opens up opportunities for developing halaqah into an online format through the Quran application for memorization. This research aims to make it easier for teachers accompanying the memorization process to monitor the memorization progress of their group members. This research uses the UX Process and Methodology method to develop an application prototype. The prototype results were tested and reviewed by 11 Al-Qur'an memorizers as participants to ensure the application design met needs. Testing techniques and measuring tools use Usability Testing and Importance Performance Analysis (IPA) to measure the level of ease of use and user acceptance of the application. The test results showed a positive response from respondents with a usability score of 71.2, which indicated that the application design was considered quite easy to use, intuitive and efficient. This research also shows that the IPA method and usability testing using Mission Usability Testing (MIUS) have succeeded in showing user behavior towards the resulting design so that it is easy to identify design positions that need to be adjusted and improved.